Familial aggregation and heritability of ankylosing spondylitis – a Swedish nested case–control study. (5th November 2019) - Morin, Matilda; Hellgren, Karin; Frisell, Thomas
Abstract: Objectives: AS is known to be a highly heritable disease, but previous studies on the magnitude of the familial aggregation and heritability of AS have been small and inconclusive, with familial relative risks ranging from 17 to 94. We aimed to improve estimates of these factors by studying families of all subjects diagnosed with AS in Sweden over a period of 16 years and to investigate if familial risks vary by sex or type of relative. Methods: In a nested case–control study, we identified AS index patients from the National Patient Register (NPR) and the Swedish Rheumatology Quality Register (SRQ) between 2001 and 2016. Each index patient was matched on age and sex to up to 50 general population controls. First-degree relatives of index patients and controls were identified through the Multi-Generation Register, with disease status ascertained in the NPR and SRQ. Familial risks were defined as odds ratios (ORs) of having AS when exposed to a first-degree relative with AS, using conditional logistic regression. Results: The overall familial OR for AS was 19.4 (95% CI 18.1, 20.8). Estimates were similar for different relative types and by sex, but having more than one affected relative resulted in a higher risk [OR 68.0 (95% CI 51.3, 90.1)]. Heritability, estimated by assuming sibling risks were completely due to genetics, was 77% (95% CI 73, 80). Conclusion: Although the familial risk and heritability of AS are higher than for most other diseases, we report estimates that are substantially lower than commonly referenced numbers for AS from other populations.